Iterative co-creation for improved hand hygiene and aseptic techniques in the operating room: experiences from the safe hands study - Annette Erichsen Andersson; Maria Frödin; Lisen Dellenborg; Lars Wallin; Jesper Hök; Brigid M. Gillespie; Ewa Wikström (BMC, 2018)
Abstract Background Hand hygiene and aseptic techniques are essential preventives in combating hospital-acquired infections. However, implementation of these strategies in the operating room remains suboptimal. There is a paucity of intervention studies providing detailed information on effective methods for change. This study aimed to evaluate the process of implementing a theory-driven knowledge translation program for improved use of hand hygiene and aseptic techniques in the operating room. Methods The study was set in an operating department of a university hospital. The intervention was underpinned by theories on organizational learning, culture and person centeredness. Qualitative process data were collected via participant observations and analyzed using a thematic approach. Results Doubts that hand-hygiene practices are effective in preventing hospital acquired infections, strong boundaries and distrust between professional groups and a lack of psychological safety were identified as barriers towards change. Facilitated interprofessional dialogue and learning in "safe spaces" worked as mechanisms for motivation and engagement. Allowing for the free expression of different opinions, doubts and viewing resistance as a natural part of any change was effective in engaging all professional categories in co-creation of clinical relevant solutions to improve hand hygiene. Conclusion Enabling nurses and physicians to think and talk differently about hospital acquired infections and hand hygiene requires a shift from the concept of one-way directed compliance towards change and learning as the result of a participatory and meaning-making process. The present study is a part of the Safe Hands project, and is registered with ClinicalTrials.gov (ID: NCT02983136 ). Date of registration 2016/11/28, retrospectively registered.